2012
DOI: 10.1121/1.4764879
|View full text |Cite
|
Sign up to set email alerts
|

Stream segregation with high spatial acuity

Abstract: Spatial hearing is widely regarded as helpful in recognizing a sound amid other competing sounds. It is a matter of debate, however, whether spatial cues contribute to "stream segregation," which refers to the specific task of assigning multiple interleaved sequences of sounds to their respective sources. The present study employed "rhythmic masking release" as a measure of the spatial acuity of stream segregation. Listeners discriminated between rhythms of noise-burst sequences presented from free-field targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 43 publications
7
77
6
Order By: Relevance
“…Nevertheless, the spectral differences tested in the present study were sufficient to produce obligatory streaming. These results are in agreement with those obtained by Middlebrooks and Onsan (2012) who parametrically measured stream segregation in the free field. They showed that voluntary streaming could be obtained in the median plane where head filtering induce subtle spectral changes which depend on position.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, the spectral differences tested in the present study were sufficient to produce obligatory streaming. These results are in agreement with those obtained by Middlebrooks and Onsan (2012) who parametrically measured stream segregation in the free field. They showed that voluntary streaming could be obtained in the median plane where head filtering induce subtle spectral changes which depend on position.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, in the anesthetized cat, Middlebrooks and Breman found an order of magnitude improvement in spatial selectivity using two concurrent but interleaved streams of rhythmic stimuli (Middlebrooks and Bremen 2013). Spatial separation of only 8°was required for individual neurons to become entrained to one of the two streams and human subjects performed well on the same task at this separation (Middlebrooks and Onsan 2012). This spatial separation compares well with the maximum performance we observed here at around 6°f or our nonstreaming, concurrent stimulus task.…”
Section: Discussionsupporting
confidence: 71%
“…When a rhythmic sequence of identical sound bursts is presented from a single location, it is perceived as one source by human observers. However, such a sequence is perceived as two sources, each with a distinct rhythm, when the sound sequences are presented from two spatially separated locations 49 . Neural correlates of this paradigm are observed in the auditory cortex of anaesthetized cats 50 .…”
Section: Hierarchical Processing In the Cortexmentioning
confidence: 99%